Proportion and Characteristics of Amino Acids Flavoring Powder for Biang Fish (Ilisha elongata) - Aulia Hidayati; Sumarto Sumarto; Suparmi Suparmi (Berkala Perikanan Terubuk, 2023)
This study aims to determine the proportions and characteristics of amino acids for the flavoring powder of the fish with different concentrations of the fish meal. The method used in this research is an experiment of making fish seasoning powder with the use of ingredients consisting of fish meal, onion, garlic, iodized salt and white pepper with a non-factorial completely randomized design consisting of 4 levels of treatment, namely P0 (0 grams of powder biang fish), P1 (60 grams of powder biang fish), P2 (70 grams of powder biang fish), P3 (80 grams of powder biang fish). The results showed that the proportion of fish meal was 23% and the analysis of types and levels of amino acids produced 9 types of essential amino acids with the highest number found in isoleucine 0.882% and 8 types of non-essential amino acids with the highest amount found in glutamic acid, namely 1,337 % .